IPTEK Pembuatan Handsanitizer serta Pemenuhan Kebutuhan Pokok Mahasiswa Terdampak Covid-19 - Rahmat Rasmawan; Masriani Masriani; Husna Amalya Melati; Hairida Hairida; Eny Enawaty; Rody Putra Sartika; Ira Lestari; Rini Muharini; Ahmad Yani T (STKIP Singkawang, 2021)
The current Covid-19 pandemic has had a very broad impact on various fields and levels of society, including education and students. Students are a group of people who are vulnerable to getting infected and becoming a COVID-19 transmitter. This Community Service activity aims to 1) Provide a deep understanding to students about covid-19 and how to prevent it. 2) Train students in making hand sanitizer and antiseptic and 3) meeting the basic needs of students affected by COVID-19. The methods used in this activity are: a) Dissemination of COVID-19 and how to prevent it. b) Assistance in the manufacture of antiseptic, including hand sanitizer and, disinfectant and, c) Providing assistance for staple food needs. Based on the results of this training activity, it shows that the participants have knowledge about what they can do to prevent the spread of Covid-19 by not traveling to places that cause crowds, always clean the boarding room or rented house with a disinfectant at least once a week and always use a hand sanitizer after having contact with objects in public areas and avoid direct physical contact such as shaking hands. Furthermore, participants have skills in making hand sanitizers and disinfectants through video tutorials made by the Community Service Team (PKM). In addition, participants were trained to maintain social distancing, especially at the stage of distributing staple food packages independently and eliminating crowds, washing hands before taking packages, measuring blood pressure, and checking body temperature.